NURSES’ PERCEPTIONS REGARDING THE INFLUENCE OF TECHNOLOGY IN CRITICAL CARE SETTINGS: A QUANTATIVE CROSS-SECTIONAL APPROACH (The Research of Medical Science Review, 2025)
Background: This research explores how nurses perceive the use of medical technology in critical care settings. Nurses are vital in patient care, and their views on technology can impact healthcare practices. The study includes both trained and non-trained nurses to understand how their education and experience shape their perceptions of technology in nursing. Knowing these differences helps us find ways to make technology more effective in nursing, ensuring it enhances patient care without making nurses overly dependent on machines. This can lead to better training programs and a balanced use of technology that supports nurses while maintaining the personal touch in healthcare.Objectives: The main objectives of this study are to: Identify the perception of nurses in critical care settings regarding the influence of technology. Assess the significance of training on nurses' perceptions. Evaluate the quality of skills, guidelines, and knowledge of nurses regarding the use of technology.Methodology: A 19-item valid questionnaire was distributed to nurses working in critical care units to gather data on their demographics, training, and views on medical technology. The Pearson chi-square test was used to analyze the relationship between training and perceptions. Data were analyzed using SPSS version 29.0.1.Results: The study found that most nurses were young, held nursing diplomas, and had limited experience in critical care. Generally, nurses had positive views of technology, highlighting its benefits for patient safety and care efficiency. However, some trained nurses expressed concerns about the potential downsides, such as increased dependence on devices and reduced personal interaction with patients. The analysis revealed no significant link between training and positive perceptions, but specific negative views were associated with training status.Conclusion: Although most nurses view technology positively,but there are concerns among trained nurses about over-reliance on devices. Training status influenced certain negative perceptions, but overall, it did not significantly impact the positive views of technology in critical care.